EFFECTIVITY OF INACTIVE GSDIV (GROUPER SLEEPY DISEASE IRIDOVIRUS) VACCINE IN GROUPER FISH (Cromileptes altivelis and Epinephelus fuscoguttatus) AGAINST GSDIV INFECTION - Ketut Mahardika; Indah Mastuti; Haryanti Haryanti (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2013)
Grouper sleepy disease iridovirus (GSDIV) has been known as viral agent causing mass mortality and significant economic losses in Indonesian aquaculture industry. The aim of this research was to know the effectivity of formalin-inactivated GSDIV vaccine to prevent GSDIV infection in humpback grouper (Cromileptes altivelis) and tiger grouper (Epinephelus fuscoguttatus). The vaccine was derived from GF cells infected-GSDIV which activated using formalin. Used vaccine was contained titer virus of 102,80-105,80 TCID50/ mL. Result of vaccination test indicated that a vaccinated grouper fish with formalininactive GSDIV vaccine should decreased mortality rate of 5%–85.4% in humpback grouper and tiger grouper that infected with GSDIV. Histopathologically, infected fish from vaccinated and control groups showed formation of enlarged cells as well as necrotized cells especially in spleen and kidney tissues. On the other hand, surviving fish from both vaccinated and control groups did not contained formation of enlarged cells in spleen, kidney, liver, and stomach.